„Biblioteki” w paleolicie - Kotuła, Sebastian Dawid (Biblioteka Uniwersytecka w Poznaniu, 2017)
Instytucje wspomagające procesy zarządzania informacją i wiedzą, jakimi są biblioteki, pojawiły się w wyniku wprowadzenia do komunikacji społecznej pisma oraz nośników pisma, a więc m.in. tabliczek glinianych, zwojów papirusowych, kodeksów pergaminowych. W bibliologii i informatologii historia bibliotek jest dobrze opracowana naukowo. Natomiast okres rozwoju ludzkości przed kulturą książki wymaga uzupełnienia. Celem niniejszego tekstu jest wykazanie, jakie metody zarządzania informacją i wiedzą stosowano przed pojawieniem się bibliotek i książek (także proto-książek). Wybrane na potrzeby artykułu przykłady pochodzą z paleolitu górnego i dotyczą wczesnych homo sapiens sapiens. Przedstawiony wywód jest wstępem do szerzej zakrojonych badań, a jego celem jest zasygnalizowanie możliwości rozszerzenia obszaru badawczego bibliologii i informatologii na okres poprzedzający narodziny bibliotek, proto-książek i książek sensu stricto.

Institutions that provide support for information and knowledge management processes such as libraries were established following the invention and progress of writing as well as tangible storage media devices in social communication such as clay tablets, papyrus scrolls, parchment codices, etc. The history of libraries has been extensively addressed and elaborated in bibliology and information science, whereas the preliteracy period, the period in the development of humankind prior to the introduction of the book culture still needs additional attention and exploration. The present article attempts to demonstrate what methods for information and knowledge management were used before libraries and books (including proto-books) appeared. The examples presented in the article come from the Upper Paleolithic and belong to an archaic type to early Homo sapiens. The following presentation is only a general overview and has introductory character. However, it provides the theoretical foundation for further more extensive studies, while its main purpose is to claim the necessity of adding completely new and expanded research areas in bibliology and information science that would cover the period prior to the emergence of libraries, proto-books and finally fully-fledged books.
“Libraries” in the Paleolithic
Keywords: metody zarządzania informacją i wiedzą; paleolit górny; proto-książki; information and knowledge management methods; Upper Paleolithic; proto-books